Inteligencia artificial en el marketing empresarial y su aplicación en las pymes registradas en la cámara de comercio del Cantón Quevedo. año 2023. - Espinoza Yépez, Ronald Denis (2024)
Many companies today are immersing themselves in an increasingly intelligent world which is an abyss of opportunities for business technology systems that now need totally solid structures to face the different changes that are occurring, one of these is artificial intelligence that is advancing by leaps and bounds leaving behind organizations that are not doing anything to adapt to the latent change. With artificial intelligence within the business networks, an improvement in the organization will be obtained in each and every one of the activities and functions where this AI is developed, now the problem remains in those organizations that are not taking measures for the application and adaptation of this great technological tool, being left aside by the strong market competition. This work was born in the need for adaptation of artificial intelligence by companies in the canton of Quevedo with fully functional and applicable tools to maximize profitability and improvement in the areas of work of the company with greater weight of its application in the marketing department since 61% of SMEs in the sector use some type of application or tool with artificial intelligence especially commercial companies that their best tool to promote their products and services is Canva, the biggest problem lies in the lack of knowledge of the management by other tools and limited to use different platforms that provide more professional services.